Case Report: A prenatal case with sex discordance between non-invasive prenatal testing and fetal genetic testings due to maternal rare chromosome karyotype - Zhong, Guoxing; Wu, Jiajia; Zhong, Zeyan; Chen, Dina; Guan, Zhiyang; Huang, Shaohui; Chen, Jianhong (Frontiers in Genetics, 2025)
BackgroundNon-invasive prenatal testing (NIPT), which made use of cell-free DNA (cffDNA) in maternal blood, was currently being applied all over the world for the detection of common chromosome abnormalities. It had relatively high sensitivity and specificity. Nevertheless, studies demonstrated that false positive results happened in 0.3% of the cases due to several factors. These factors included confined placental mosaicism, maternal mosaicism, maternal transfusions, maternal malignancy, vanishing twins and maternal chromosomal abnormalities.Case reportWe presented a case of a 27-year-old healthy woman, who had a high risk of trisomy 21 syndrome in first-trimester serum screening at 12 gestational weeks. The result of NIPT indicated a high risk of klinefelter syndrome (47, XXY) at 15 weeks gestation. Subsequently, amniocentesis revealed a normal female fetus karyotype (46, XX) at 18 weeks gestation. Discordant sex chromosome results emerged. Eventually, it was discovered that there was a rare maternal karyotype 46,X,der(X)t (X; Y) (p22.3; q11.2), which led to the sex discrepancy between the NIPT and the fetal prenatal diagnostic results.ConclusionWe presented a case in which there was a sex discrepancy between NIPT and fetal genetic testing due to a rare chromosome karyotype in the mother. NIPT was merely a prenatal screening test. Consequently, patients who had a screen-positive result for a chromosomal anomaly following NIPT ought to be properly counselled and advised to undergo an invasive diagnostic procedure for confirmation.